Pengembangan media pembelajaran dengan pendekatan saintifik menggunakan software geogebra - Afiyah, Nada Al; Pertiwi, Citra Megiana; Hidayat, Wahyu (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
his study aims to find out the process of learning media development, the feasibility of the learning media developed, the effectiveness of the learning media, and the obstacles encountered during the learning media development process. The method used in this study is the R&D (Research and Development) method by implementing the steps of the 4D development research model. The subjects in the study consisted of all students of class XI A and class XI B at one of the schools in Bandung. From the results of the feasibility test conducted by validators, practitioners, and students, it can be seen that the learning media is suitable for use in learning, namely 89% showing that the learning media is in the valid category